Potensi Industri Halal di Indonesia sebagai Negara Berpenduduk Muslim Terbesar - Humaida, Afif; Fasicha, Ilmadian; Alghifari, M. Ifanal; Lestari, Pujisri (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2024)
The halal industry has enormous potential in Indonesia. This is due to the large population of Muslims in Indonesia. We can see the potential of Indonesia's halal industry in several fields, including halal food. Halal food is a basic need for Muslims. The aim of this research is to analyze the potential of the Halal Industry in Indonesia as a country with the largest Muslim population. Indonesia has great potential to become a major player in the global halal industry. However, this requires appropriate and accurate strategies, as well as support from the government, economic actors and other stakeholders. The research uses a qualitative approach with a type of literature study, data sources obtained from documentation, book records, journals, etc. Data analysis was carried out using descriptive qualitative approach techniques. The results of this research show that the halal industry includes the acquisition of raw materials, processing and production in accordance with halal standards. Indonesia has great potential in the halah industry, including in the halal food, fashion and finance industries, considering that the majority of Indonesia's population is Muslim. Indonesia is the largest consumer of halal products.